2012
DOI: 10.15803/ijnc.2.1_131
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of AES encryption on CUDA GPU

Abstract: GPU exhibits the capability for applications with a high level of parallelism despite its low cost. The support of integer and logical instructions by the latest generation of GPUs enables us to implement cipher algorithms more easily. However, decisions such as parallel processing granularity and memory allocation impose a heavy burden on programmers. Therefore, this paper presents results of several experiments that were conducted to elucidate the relation between memory allocation styles of variables of AES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 6 publications
1
39
0
1
Order By: Relevance
“…The effect of the number of threads and file size are also shown. Iwai et al [17] further discussed granularity and the variety of memory allocations for variables of cipher programs. It showed that efficient CUDA programs made a difference of more than 50 times in performance.…”
Section: Optimization For Cipher Programs On Gpgpumentioning
confidence: 99%
See 3 more Smart Citations
“…The effect of the number of threads and file size are also shown. Iwai et al [17] further discussed granularity and the variety of memory allocations for variables of cipher programs. It showed that efficient CUDA programs made a difference of more than 50 times in performance.…”
Section: Optimization For Cipher Programs On Gpgpumentioning
confidence: 99%
“…It showed that efficient CUDA programs made a difference of more than 50 times in performance. Nishikawa et al [18], [19] applied the technique shown in [17] to other ciphers to validate the effectiveness of it. The result showed that implemented ciphers, Camellia, CIPHERUNICORN-A, Misty, and SC2000 also exhibit high-performance.…”
Section: Optimization For Cipher Programs On Gpgpumentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper we consider an XSL block cipher implementation over the finite field GF (2 8 ) with MDS-matrix linear transform and block-size 128 bit. We present different algorithmic optimization of this algorithm.…”
Section: Introductionmentioning
confidence: 99%